Recent Malaysian food waste generation trends, enacted policies and challenges in food waste management / Hasyireen Abdul Halim, Nursahizalina Mohd Sa’at and Rozieana Abu - Abdul Halim, Hasyireen; Mohd Sa’at, Nursahizalina; Abu, Rozieana (Penerbit UiTM (UiTM Press), 2025)
Food waste (FW) presents a significant global challenge, particularly in Malaysia, where guidance on waste composition and management issues remains limited. This review examines current trends, policies, and obstacles in managing FW in Malaysia by systematically analyzing a range of publications and conference proceedings from the last 15 years (2008-2023). The methodology involved a comprehensive literature review, focusing on studies that address FW management practices and its challenges, technological advancements, and policy frameworks. Key challenges identified include incomplete data, low public awareness, underdeveloped digestion technologies, and insufficient knowledge of FW treatment methods. Effective FW management is contingent upon enhancing public awareness, improving waste segregation, and upgrading infrastructure. In light of current practices and policies, this review proposes an integrated management framework that combines wet anaerobic digestion with aerobic windrow composting, leading to the conversion of FW into biogas and final landfilling. This approach aims to minimize landfill dependency and promote a circular economy by transforming FW into renewable energy sources.